2013
DOI: 10.1007/s00134-013-3153-z
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in the ICU: relief of pain, dyspnea, and thirst—A report from the IPAL-ICU Advisory Board

Abstract: Purpose Pain, dyspnea, and thirst are three of the most prevalent, intense, and distressing symptoms of intensive care unit (ICU) patients. In this report, the interdisciplinary Advisory Board of the Improving Palliative Care in the ICU(IPAL-ICU) Project brings together expertise in both critical care and palliative care along with current information to address challenges in assessment and management. Methods We conducted a comprehensive review of literature focusing on intensive care and palliative care re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
127
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 101 publications
1
127
0
11
Order By: Relevance
“…3,4,8,46,47 Prior work emphasizes the importance of care provision by clinicians with expertise in palliative care, 47 yet palliative care consultation services cannot see all seriously ill ICU patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,8,46,47 Prior work emphasizes the importance of care provision by clinicians with expertise in palliative care, 47 yet palliative care consultation services cannot see all seriously ill ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…41-43 Some of our sites have expanded the IMPACT-ICU program to include participants from other disciplines. We hope that training of ICU clinicians, in conjunction with integration of palliative care processes into routine practice, 44 will influence aspects of palliative care that did not improve with our program, such as identification of uncontrolled symptoms.Our work is significant, considering the growing focus on ICU palliative care, [3][4][5][6][7][8][9][10][45][46][47] for which a number of models exist. 3,4,8,46,47 Prior work emphasizes the importance of care provision by clinicians with expertise in palliative care, 47 yet palliative care consultation services cannot see all seriously ill ICU patients.…”
mentioning
confidence: 99%
“…Titrating to the patient's responses with a low-and-slow regimen is recommended. 3 Mechanical ventilation, invasive or noninvasive, is an effective means of treating dyspnea associated with respiratory failure. Yet, dying patients generally want to forgo mechanical ventilation.…”
Section: Treatmentmentioning
confidence: 99%
“…2 Dyspnea is akin to suffocation and is one of the worst symptoms experienced by critically ill patients, including those who are receiving mechanical ventilation. 3,4 …”
mentioning
confidence: 99%
“…While one large trial of an integrative ICU-based palliative care approach studied in 22 French ICUs was associated with significant decreases in family member anxiety, depression, and post-traumatic stress disorder levels [14], only a handful of ICU-based palliative care studies [15][16][17] have measured family-reported outcomes other than ''family satisfaction''. Moreover, ICU-based palliative care trials have thus far not measured truly patient-centered outcomes, such as symptom scores or quality of life [18].…”
mentioning
confidence: 99%